English Training For Sunday School Of Gmim Tabur Kasih Malalayang Manado - Samola, N F R (Journal of Educational Method and Technology, 2018)
Facing era of globalization needs people to prepare human resources mainly in the sector of science and technology. To have a good mastery of technology someone requires sufficient knowledge in facing global world needs which is known as a competitive era. In this case,the role of English or other foreign languages is very important in mastering communication technology or even for direct communication using English. English is not only fulfilling academic purposes since the mastery is only focused on the knowledge of the language itself, however it is used as a tool of global communication. This supports the Indonesian government program of Visit Indonesia and Pesona Indonesia for the purpose of developing the prosperity of Indonesian society. As cityzens of Manado, the capital city of North Sulawesi, is supporting the program by giving special attention to the early age of school; Sunday School Children of Tabur Kasih Malalayang teaching them simple and practical English sentences and vocabularies. English Nursary Rhymes including songs were chosen as teaching media. This training was aimed at giving the children simple English sentenses and vocabularies. The training was done in Manado Tabur Kasih Congregation attended by 30 children. Keywords: English training, Sunday School Children